العولمة وعلاقتها بالتحديث والتنمية السياسية في دول العالم الثالث - إبراهيمد.ابراهيم ابوصلاح (Aljameai, 2025)
المستخلص تتناول هذه الدراسة الإشكالية المعقدة لتداخل تأثيرات العولمة مع مسارات التحديث والتنمية السياسية في دول العالم الثالث، باستخدام الحالة الليبية كنموذج تحليلي. تنطلق من إشكالية رئيسية تتمثل في كيفية تشكّل العلاقة الجدلية بين العولمة كمشروع هيمنة خارجي، والتحولات الداخلية المرتبطة بالتنمية السياسية في دولة ريعية ذات خصوصية تاريخية وسياسية مثل ليبيا. وتكمن أهمية الدراسة في سعيها لتقديم قراءة نقدية تكشف عن التداخل بين العوامل الداخلية والخارجية المفسرة لأزمة التنمية السياسية، متجاوزةً التحليلات الأحادية الجانب. تهدف الورقة إلى تحليل الأبعاد النظرية للعولمة وتفاعلاتها مع مفاهيم التحديث والتنمية، وتشريح تجليات هذه الأبعاد في السياقين العربي والليبي، وتقييم أثرها على بناء الدولة والهوية المجتمعية، واستشراف إمكانيات التحول الديمقراطي. وتبنى على فرضية مفادها أن العولمة قد ساهمت، عبر آلياتها غير المتكافئة، في تعميق التناقضات البنيوية الداخلية في ليبيا، مما أدى إلى تشويه مسار التحديث وإعاقة إمكانية قيام تنمية سياسية حقيقية، وتحوّلت من إطار ضاغط إلى عامل فاعل في تفكك الدولة واستدامة أزمتها بعد 2011. واعتمدت الدراسة المنهج الوصفي التحليلي والتاريخي، مع الاعتماد على مراجعة الأدبيات وتحليل الوثائق. وتخلص إلى أن التنمية السياسية في السياقات الهشة مثل الليبي لا يمكن أن تكون نتاجاً لضغوط العولمة الخارجية فحسب، بل تحتاج إلى مشروع داخلي توافقي يعيد بناء الشرعية على أساس المواطنة والمؤسسات، ويُفاعل مع المنظومة العالمية بانتقائية وذكاء. Abstract: This study addresses the complex problematic of how globalization’s influences intertwine with the trajectories of modernization and political development in Third World countries, using the Libyan case as an analytical model. It stems from a central research problem concerning the nature of the dialectical relationship between globalization as an external hegemonic project and the internal transformations associated with political development in a rentier state with unique historical and political characteristics like Libya. The significance of the study lies in its endeavor to provide a critical reading that reveals the interplay between internal and external factors explaining the crisis of political development, moving beyond one-sided analyses. The paper aims to analyze the theoretical dimensions of globalization and their interactions with concepts of modernization and development, dissect the manifestations of these dimensions in the Arab and Libyan contexts, assess their impact on state-building and societal identity, and explore possibilities for democratic transformation. It is built on the hypothesis that globalization, through its unequal mechanisms, has contributed to deepening the internal structural contradictions in Libya, leading to a distortion of the modernization path and hindering the possibility of genuine political development. It transformed from a constraining framework into an active factor in the state’s disintegration and the perpetuation of its crisis post-2011. The study adopted the descriptive-analytical and historical methods, relying on a review of literature and document analysis. It concludes that political development in fragile contexts like Libya cannot be merely a product of external globalization pressures. Instead, it requires an internal consensual project that rebuilds legitimacy based on citizenship and institutions, and engages with the global system selectively and intelligently.